Family perceptions and efforts in preventing malnutrition (stunting) health problems in children in mandailing natal regency - Nasution Siti Saidah (BIO Web of Conferences)
Stunting is a chronic issue of malnutrition in children, caused by prolonged inadequate nutritional intake and the provision of food that does not meet their dietary needs. Family perceptions of stunting are closely related to the treatment approaches and efforts to address the problem. Madina Regency, located in North Sumatra, is one of the regions with a high prevalence of stunting. This study aimed to examine the perceptions of families and communities in the Mandailing Natal district regarding stunting and identify the efforts to prevent stunting in children. The study population consisted of all families in the Madina Regency area with children under five. A total of 265 respondents participated in the study. Data were collected using a questionnaire that included sections on demographic data, family perceptions, and preventive efforts. The data were analyzed using univariate frequency distributions and presented as percentages. The results revealed that 85 respondents (32.07%) had positive perceptions of stunting, while 180 respondents (67.93%) exhibited negative perceptions. Regarding family efforts to prevent stunting, 47 respondents (17.74%) were categorized as making reasonable efforts, 98 respondents (26.98%) as making moderate efforts, and 120 respondents (45.28%) as making insufficient efforts. These findings highlight the need for targeted interventions, such as counselling and educational programs for families, to improve awareness and promote practical actions to prevent stunting. The predominance of negative perceptions and insufficient efforts underscores the importance of health education initiatives in addressing this critical issue.